Case report: Atypical patterns of nystagmus suggest posterior canal cupulolithiasis and short-arm canalithiasis - Helminski, Janet O. (Frontiers in Neurology, 2022)
Background Atypical posterior canal (PC) positional nystagmus may be due to the changes in cupular response dynamics from cupulolithiasis (cu), canalithiasis of the short arm (ca-sa), or a partial/complete obstruction—jam. Factors that change the dynamics are the position of the head in the pitch plane, individual variability in the location of the PC attachment to the utricle and the position of the cupula within the ampulla, and the location of debris within the short arm and on the cupula. The clinical presentation of PC-BPPV-cu is DBN with torsion towards the contralateral side in the DH positions and SHHP or no nystagmus in the ipsilateral DH position and no nystagmus upon return to sitting from each position. The clinical presentation of PC-BPPV-ca-sa is no nystagmus in the DH position and upbeat nystagmus (UBN) with torsion lateralized to the involved side upon return to sitting from each position. Case description A 68-year-old woman, diagnosed with BPPV, presented with DBN associated with vertigo in both DH positions and without nystagmus or symptoms on sitting up. In the straight head hanging position (SHHP), the findings of a transient burst of UBN with left torsion associated with vertigo suggested ipsicanal conversion from the left PC-BPPV-cu to canalithiasis. Treatment included a modified canalith repositioning procedure (CRP), which resulted in complete resolution. BPPV recurred 17 days later. Clinical presentation of BPPV included no nystagmus/symptoms in both the contralateral DH position and SHHP, DBN in the ipsilateral DH position without symptoms, and UBN with left torsion associated with severe truncal retropulsion and nausea on sitting up from provoking position. The findings suggested the left PC-BPPV-cu-sa and PC-BPPV-ca-sa. Treatment included neck extension, a modified CRP, and demi-Semont before complete resolution. Conclusion An understanding of the biomechanics of the vestibular system is necessary to differentially diagnose atypical PC-BPPV. DH test (DHT) findings suggest that PC-BPPV-cu presents with DBN or no nystagmus in one or two DH positions and sometimes SHHP and without nystagmus or no reversal/reversal of nystagmus on sitting up. The findings suggest PC-BPPV-ca-sa has no nystagmus in DH positions or DBN in the ipsilateral DH position and UBN with torsion lateralized to the involved side on sitting up.